Primary biliary cirrhosis and the nuclear pore complex (2012)
Experimental models of autoimmune diseases have led to the conclusion that an immune response to nuclear antigens is a sentinel marker for loss of tolerance and potential tissue damage. Various proteins are targets of antinuclear antibodies in a variety of autoimmune diseases, ranging from systemic rheumatologic disorders to diseases affecting specific organs such as the liver. Autoantibodies against specific nuclear constituents have also been used as probes to understand the structure and the function of the targeted components and their relevance to disease pathogenesis. Approximately a quarter of patients with primary biliary cirrhosis (PBC) have antibodies targeting proteins of the nuclear pore complex (NPC), a multi-protein structure that mediates molecular transport across the nuclear envelope. Autoantibodies against the integral membrane glycoprotein gp210 and nucleoporin p62 appear to be highly specific for PBC, an autoimmune disease characterized by progressive destruction of intrahepatic biliary epithelial cells. This review discusses the diagnostic and clinical relevance of anti-NPC antibodies in PBC and the possibility that this autoimmune response may arise as a result of molecular mimicry. © 2012 Elsevier B.V.